GENERAL ASPECTS REGARDING THE IMPORTANCE OF GOALKEEPER TECHNIQUE IN FOOTBALL GAME FOR CHILDREN AGED 12-13 - Tatarcan Catalin Andrei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
As a result of the application of specific exercises to the goalkeepers, detailed below, we noticed an improvement in the technique specific to that position (goalkeeper). We used elements and technical procedures for catching, diving and throwing the ball specific to goalkeepers. The study shows that the efficiency of the goalkeepers in the target group is higher, the number of goals received after the test being lower than those in the control group. The children subjected to the test are players from the Luceafărul Bucovina Club.